Does Gender Diversity Promote Nonconformity? - Amini, Makan; Ekström, Mathias; Ellingsen, Tore; Johannesson, Magnus; Strömsten, Fredrik (Management Science, 2017)
Failure to express minority views may distort the behavior of company boards, committees, juries, and other decision-making bodies. Devising a new experimental procedure to measure such conformity in a judgment task, we compare the degree of conformity in groups with varying gender composition. Overall, our experiments offer little evidence that gender composition affects expression of minority views. A robust finding is that a subject’s lack of ability predicts both a true propensity to accept others’ judgment (informational social influence) and a propensity to agree despite private doubt (normative social influence). Thus, as an antidote to conformity in our experiments, high individual ability seems more effective than group diversity. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2015.2382 . This paper was accepted by John List, behavioral economics.